Optimalisasi Pelayanan Kepolisian Dalam Upaya Menangani Pengaduan Tindak Pidana Kriminal ( Studi Kasus Kecamatan Mendoyo) - Puspadana, Ni luh Ayu Virly; Noak, Piers Andreas; Winaya, I Ketut (CITIZEN CHARTER, 2015)
ABSTRACT Mendoyo sub-districts is the most extensive sub-districts in the district of Jembrana. Therefore this sub-districts very potentially give high crime action. High crime rate that occurred in the sub-districts Mendoyo start making people wroth, so that people begin to make a reaction to eradicate the problem of criminality, one way to do criminal complaint to the police.In this study will examine how optimization services a criminal offense criminal from the public by the police, by using descriptive qualitative research method. The results of this study indicate that the service is implemented by the police is not optimal, it is in because there are several dimensions of service quality according to Lovelock and Wright, Zeithaml and Bitner, such as Assurance and Tangibles. Keywords : Police, Service, Complaint, The Crime of Criminal